Towards comprise the Design System Applicability: A Multivocal Literature Mapping - Vendramini, Sara; Belusso, Luana; Souza, Francisco Carlos; Souza, Alinne (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
During the software development process, the standardization lack and consistency of software products are still present in companies. In this sense, considerable attention has been paid to Design System since it seeks to improve the software development process making their products more consistent and scalable. This study presents a Multivocal Literature Mapping that summarizes, analyzes, and characterizes the state-of-the-art Design System. We analyzed 23 sources to identify key elements, essential resources, the main developer’s needs that lead to adopting a Design System, the proposed solutions of the Design System, and the impacts generated from this use. The results are based on 23 sources, from which 17 are sources in the gray literature and six are formally published sources. Summarizing on Design System, our Multivocal Literature Mapping identified four types of elements, three resources, seven different developer’s needs, four solutions, and seven impacts generated from the Design System. Our findings show that this research is a starting point to understand the best strategies for adopting the Design System among software companies. We also concluded that the needs, solutions, and impacts in the adoption of the Design System identified in this Multivocal Literature Mapping can assist companies to improves the quality of their software products.